2017
DOI: 10.1097/spv.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Age Is a Risk Factor for Decreased Postpartum Pelvic Floor Strength

Abstract: Objectives To determine factors associated with decreased pelvic floor strength (PFS) after the first vaginal delivery in a cohort of low risk women Methods This is a secondary analysis of a prospective study examining the risk of pelvic floor injury in a cohort of primiparous women. All recruited participants underwent an examination, 3D ultrasound and measurement of pelvic floor strength (PFS) in the third trimester and repeated at 4 weeks-6 months postpartum using a perineometer. Results There were 84 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Some sociodemographic characteristics may have an effect on PFM strength. Some studies have reported that aging may lead to a decrease in mechanical strength and predispose an individual to prolapse, UI and sexual dysfunction [29][30][31][32]. Likewise, in our study, the PFM rapid, tonic, and endurance contraction amplitudes all decreased when age increased.…”
Section: Discussionsupporting
confidence: 76%
“…Some sociodemographic characteristics may have an effect on PFM strength. Some studies have reported that aging may lead to a decrease in mechanical strength and predispose an individual to prolapse, UI and sexual dysfunction [29][30][31][32]. Likewise, in our study, the PFM rapid, tonic, and endurance contraction amplitudes all decreased when age increased.…”
Section: Discussionsupporting
confidence: 76%
“…In a study that used ultrasound to investigate the extent of levator ani damage in low-risk primiparous women based on age found an inverse relationship between age and severity of levator ani damage. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The weakness of the pelvic floor muscles (PFMs) is a common cause of pelvic floor dysfunction after childbirth 3 . Pregnancy, vaginal birth, parity, duration of the second stage of labor, difficulty extracting the fetus during a cesarean section (CS), infant weight, perineal trauma, and other mechanical, endocrine, and neural factors can lead to reduction or loss of pelvic floor muscle tone causing genitourinary disorders 4 - 7 .…”
Section: Introductionmentioning
confidence: 99%